All Health Care is Not Local: An Evaluation of the Distribution of Emergency Department Care Delivered in Indiana - Finnell, John T. (American Medical Informatics Association, 2011)
The Emergency Department (ED) delivers a major portion of health care – often with incomplete knowledge about the patient. As such, EDs are particularly likely to benefit from a health information exchange (HIE). The Indiana Public Health Emergency Surveillance System (PHESS) sends real-time registration information for emergency department encounters. Over the three-year study period, we found 2.8 million patients generated 7.4 million ED visits. The average number of visits was 2.6 visits/patient (range 1–385). We found more than 40% of ED visits during the study period were for patients having data at multiple institutions. When examining the network density, we found nearly all EDs share patients with more than 80 other EDs. Our results help clarify future health care policy decisions regarding optimal NHIN architecture and discount the notion that ‘all healthcare is local’.